Formulation of a bacterial - silt mixture for degrading hydrocarbons in crude oil-contaminated sediments - Hii Yii Siang (Terengganu: Universiti Putra Malaysia Terengganu, 2014)
Bacterial-silt mixture has been formulated to degrade hydrocarbons in crude oil contaminated sediments (1500 mg/kg Petronas Tapis A crude oil). The bacterial-silt mixture was formulated by inoculating an active oil degrading bacteria isolated from Malaysia marine environment into enriched marine silt. The spores forming characteristic of this active oil degrading bacteria has made the formulated mixture a success.